Estudo do potencial enzimático hidrolítico e oxidativo do microorganismo Myceliophthora thermophila M.7.7 - Santos, Hévila Brognaro dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In terms of the here presented PhD research project the hydrolytic and oxidative enzymatic properties from the ascomycota and themotolerant fungae Myceliophthora thermophila M.7.7. were investigated in detail. Six different secretomes were analysed by mass spectroscopy and 187 proteins were identified. Within these proteins beside already known and expected enzymes also several oxidative active enzymes were confirmed. Enzymes belonging to the cellobiose dehydrogenase and glycoside hydrolase family 7 were most abundant, when in natura and steam exploded sugar cane bagasses were used as carbon source. Particular a high abundance of glycoside hydrolases was identified when a mixture of hemicelluloses was applied as sole carbon source. In this case the secretome analysis showed a substrate-specific secretion for this fungae. The isolation, purification and characterization of a β-glycosidase from M. thermophila M.7.7. showed and confirmed excellent enzymatic charateristics and parameters for future potential applications as a supplemental enzyme in enzyme cocktails, or implimanting by molecular biology in organisms deficient in β-glucosidase. Even at low protein concentration the enzymatic hydrolysis, utilizing the crude extract, resulted in a conversion of approx. 21% in natura bagasse and approx. 16% in commercial cellulose, indicating a high specificity and synergy of the enzyme complex to cellulose polymers with a higher degree of polymerization and crystallinity index in its structure

Neste trabalho foram estudados os sistemas enzimáticos hidrolítico e oxidativo do ascomiceto termotolerante Myceliophthora thermophila M.7.7. Seis diferentes secretomas foram avaliados por espectroscopia de massas que identificou o total de 187 proteínas confirmando a presença do clássico sistema enzimático hidrólitico revelando também a produção de enzimas do sistema oxidativo de degradação. As enzimas mais abundantes foram celobiose desidrogenase e glicosídeo hidrolase família 7 secretadas principalmente nos bagaços de cana-de-açúcar in natura e explodido a vapor. A abundante produção de glicosídeo hidrolases foi identificada quando polissacarídeos de hemiceluloses foram a fonte de carbono empregada, mostrando que o produção de enzimas é substrato específica. O isolamento, a caracterização bioquímica e o estudo cinético enzimático de uma β-glicosidase do M. thermophila M.7.7. também foram realizados. A β-glicosidase purificada apresentou excelentes parâmetros para sua aplicabilidade como enzima suplementar a coquetéis enzimáticos ou até mesmo sua clonagem e expressão em organismos deficientes em β-glicosidase. Experimentos de hidrolíse enzimática também foram executados empregando o extrato bruto de M. thermophila, que resultou em uma conversão de 21% em bagaço in natura e 16% em celulose comercial mesmo com baixa carga de proteínas, indicando maior especificidade e sinergia do complexo enzimático à polímeros de celulose com maior índice de cristalinidade e grau de polimerização em sua estrutura
Keywords: Biologia molecular; Biofísica; Enzimas; Biomassa; Espectrometria de massa; Cinetica de enzimas; Biophysics